Can the Pirani Score Predict the Number of Casts and the Need for Tenotomy in the Management of Clubfoot by the Ponseti Method? - Sharma, A (Malays Orthop J, 2018)
Introduction: We assessed the role of the Pirani score in determining the number of casts and its ability to suggest requirement for tenotomy in the management of clubfoot by the Ponseti method. Materials and Methods: Prospective analysis of 66 (110 feet) cases of idiopathic clubfoot up to one year of age was done. Exclusion criteria included children more than one year of age at the start of treatment, non-idiopathic cases and previously treated or operated cases. Results: The initial Pirani score was (5.5±0.7) for the tenotomy group and the initial Pirani score was (3.3±1.6) for the non-tenotomy group. There was a significant difference between the initial Pirani score for the tenotomy and the non-tenotomy group with t= -7.9, df= 64 p<0.0001. The tenotomy group had a significantly higher number of casts (four to seven) compared to non-tenotomy group (two to five) t=-10.4, df=64, p<0.0001. Spearman’s rank correlation coefficient was significant and confirmed positive correlation between the initial Pirani score and the number of casts required to correct the deformity (r = 0.931, p<0.0001). Conclusion: Initial high Pirani score suggests the need for greater number of casts to achieve correction and probable need for tenotomy. The number of casts required in achieving complete correction increases with increase in the initial Pirani score. The initial high hindfoot score (2.5-3) signifies the probable need of a minor surgical intervention of percutaneous tendoachilles tenotomy. Based on the initial Pirani score, parents can be informed about the probable duration of treatment and the need for tenotomy.